The environmental education of the students in the primary schools in the Republic of Macedonia - Srbinovski, Mile (Macedonian Journal of Ecology and Environment, 2003)
The goal of this work is to confirm the level of the environmental education of the students in the primary schools in the Republic of Macedonia through cognitive, valuable, affective and conative ecological component. The same is done with 5 instruments with relatively good metric characteristics on sample of 515 students from 19 primary schools of Republic. The results are present in this paper.